Associations of clustered health risk behaviors with diabetes and hypertension in White, Black, Hispanic, and Asian American adults - Won Kim Cook; Libo Li; Christina C. Tam; Nina Mulia; William C. Kerr (BMC Public Health, 2022)
Abstract Background The clustering of Big Four contributors to morbidity and mortality—alcohol misuse, smoking, poor diet, and physical inactivity—may further elevate chronic health risk, but there is limited information about their specific combinations and associated health risks for racial/ethnic minority groups. We aimed to examine patterns of clustering in risk behaviors for White, Black, Hispanic, and Asian American adults and their associations with diabetes and hypertension. As these behaviors may be socioeconomically-patterned, we also examined associations between clustering and socioeconomic status (SES). Methods Latent class analyses and multinomial and logistic regressions were conducted using a nationally-representative sample of United States (US) adults ages 40–70 (N = 35,322) from Waves 2 (2004–2005) and 3 (2012–2013) of the National Epidemiologic Survey on Alcohol and Related Conditions. Obesity was used as a proxy for unhealthy diet. The outcomes were diabetes and hypertension. Results A relatively-healthy-lifestyle class was found only among White adults. Common patterns of unhealthy clustering were found across groups with some variations: the obese-inactive class among White, Black, and Hispanic adults (and the inactive class among Asian adults); the obese-inactive-smoking class among White, Black, and Hispanic adults; the smoking-risky-drinking class among White and Hispanic adults; and the smoking-risky-drinking-inactive class among Black and Asian adults. Positive associations of unhealthier clustering (having a greater number of risk behaviors) with lower SES (i.e., family income and education) and with health conditions were more consistent for Whites than for other groups. For racial minority groups, lower education than income was more consistently associated with unhealthy clusters. The associations between unhealthier clustering and diabetes and hypertension were less clear for Blacks and Asians than for Whites, with no significant association observed for Hispanics. Conclusion Concerted efforts to address clustered risk behaviors in most US adults, particularly in racial/ethnic minority groups given the high prevalence of unhealthy clustering, are warranted.